Trail of Bones : More Cases from the Files of a Forensic Anthropologist - Manhein, Mary H. (Mary Huffman) (Book collections on Project MUSE., 2005)
A fellow of the American Academy of Forensic Sciences and an expert on the human skeleton, Mary H. Manhein assists law enforcement officials across the country in identifying bodies and solving criminal cases. In Trail of Bones, her much-anticipated sequel to The Bone Lady, Manhein reveals the everyday realities of forensic anthropology. Going beyond the stereotypes portrayed on television, this real-life crime scene investigator unveils a gritty, exhausting, exacting, alternately rewarding and frustrating world where teamwork supersedes individual heroics and some cases unfortunately remain u.